Consolidated Bioprocessing for Butyric Acid Production from Rice Straw with Undefined Mixed Culture - Ai, Binling; Chi, Xue; Meng, Jia; Sheng, Zhanwu; Zheng, Lili; Zheng, Xiaoyan; Li, Jianzheng (Frontiers in Microbiology, 2016)
Lignocellulosic biomass is a renewable source with great potential for biofuels and bioproducts. However, the cost of cellulolytic enzymes limits the utilization of the low-cost bioresource. This study aimed to develop a consolidated bioprocessing without the need of supplementary cellulase for butyric acid production from lignocellulosic biomass. A stirred-tank reactor with a working volume of 21 L was constructed and operated in batch and semi-continuous fermentation modes with a cellulolytic butyrate-producing microbial community. The semi-continuous fermentation with intermittent discharging of the culture broth and replenishment with fresh medium achieved the highest butyric acid productivity of 2.69 g/(L•d). In semi-continuous operation mode, the butyric acid and total carboxylic acid concentrations of 16.2 and 28.9 g/L, respectively, were achieved. Over the 21-day fermentation period, their cumulative yields reached 1189 and 2048 g, respectively, corresponding to 41% and 74% of the maximum theoretical yields based on the amount of NaOH pretreated rice straw fed in. This study demonstrated that an undefined mixed culture-based consolidated bioprocessing for butyric acid production can completely eliminate the cost of supplementary cellulolytic enzymes.